The making of the modern refugee - Gatrell, Peter (Oxford : Oxford University Press, 2013)
"The Making of the Modern Refugee is a comprehensive history of global population displacement in the twentieth century. It takes a new approach to the subject, exploring its causes, consequences, and meanings. History, the author shows, provides important clues to understanding how the idea of refugees as a "problem" embedded itself in the minds of policy-makers and the public, and poses a series of fundamental questions about the nature of enforced migration and how it has shaped society throughout the twentieth century across a broad geographical area--from Europe and the Middle East to South Asia, South-East Asia and sub-Saharan Africa. Wars, revolutions, and state formation are invoked as the main causal explanations of displacement, and are considered alongside the emergence of a twentieth-century refugee regime linking governmental practices, professional expertise, and humanitarian relief efforts."--Jacket.
pt. I EMPIRES OF REFUGEES -- Introduction -- 1. Crucibles of Population Displacement Before and During the Great War -- 2. Nation-states and the Birth of a 'Refugee Problem' in Inter-war Europe -- pt. II MID-CENTURY MAELSTROM -- Introduction -- 3. Europe Uprooted: Refugee Crises at Mid-Century and 'Durable Solutions' -- 4. 'Nothing Except Commas: Jews, Palestinians, and the Torment of Displacement -- 5. Midnight's Refugees?: Partition and its Aftermath in India and Pakistan -- 6. War and Population Displacement in East Asia, 1937-1950 -- pt. III REFUGEES IN THE GLOBAL COLD WAR AND ITS AFTERMATH -- Introduction -- 7. 'Villages of Discipline': Revolutionary Change and Refugees in South-East Asia -- 8. 'Long Road': Africa's Refugees, Decolonization, and 'Development' -- 9. 'Some Kind of Freedom': Refugees, Homecoming, and Refugee Voices in Contemporary History.
Includes bibliographical references and index.
Keywords: 1900-1999; REFUGEES--HISTORY -- 20th century; REFUGEES--FAST; HUMAN LIFE; INTERNATIONAL POLITIC; Europa; Electronic books; History